2008
DOI: 10.1016/j.cytogfr.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Interferon and cytokine responses to SARS-coronavirus infection

Abstract: The sudden emergence of severe acute respiratory syndrome (SARS) has boosted research on innate immune responses to coronaviruses. It is now well established that the causative agent, a newly identified coronavirus termed SARS-CoV, employs multiple passive and active mechanisms to avoid induction of the antiviral type I interferons in tissue cells. By contrast, chemokines such as IP-10 or IL-8 are strongly upregulated. The imbalance in the IFN response is thought to contribute to the establishment of viremia e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
150
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(158 citation statements)
references
References 175 publications
(263 reference statements)
5
150
0
3
Order By: Relevance
“…Mice infected with the H1N1 virus were reported to exhibit different courses of ARDS and led to cytokine storm in the body (Garigliany et al, 2010). It is well known that cytokine storm plays a major role in pneumonia and ARDS (Thiel and Weber, 2008). The clinical study showed a slight increase of IL-6, IL-10 and TNF-α and high levels of IFN-γ and MCP-1 in patients with ARDS caused by H1N1 infection (Bermejo-Martin et al, 2009;Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mice infected with the H1N1 virus were reported to exhibit different courses of ARDS and led to cytokine storm in the body (Garigliany et al, 2010). It is well known that cytokine storm plays a major role in pneumonia and ARDS (Thiel and Weber, 2008). The clinical study showed a slight increase of IL-6, IL-10 and TNF-α and high levels of IFN-γ and MCP-1 in patients with ARDS caused by H1N1 infection (Bermejo-Martin et al, 2009;Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The innate immune response is critical for host defence against respiratory coronaviruses (CoVs) (Charley et al , 2006; Frieman et al , 2008; Thiel & Weber, 2008). Most CoVs are sensitive to the antiviral effects of virus-induced IFN-α/β.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the group 1 CoVs in the family Coronaviridae , order Nidovirales , PRCV and transmissible gastroenteritis virus (TGEV) are potent IFN-α inducers (Charley et al , 2006; Van Reeth et al , 1999; Zhang et al , 2008). The recently identified human CoV, severe acute respiratory syndrome coronavirus (SARS)-CoV, which belongs to subgroup 2b of the group 2 CoVs (Kuiken et al , 2003; Lau et al , 2005; Saif, 2004), also elicits type I interferons (IFNs), but it may also evade their antiviral activity (Frieman et al , 2008; Thiel & Weber, 2008). The innate immune responses of the host against respiratory viruses involve alveolar macrophages, pulmonary epithelial cells, natural killer (NK) cells, dendritic cells and IFN-α/β responses in the lung.…”
Section: Introductionmentioning
confidence: 99%
“…The production and action of type I interferons, which are major components of antiviral innate immunity (2,3), are inhibited at multiple levels by SARS coronavirus (4,5). This inhibition is thought to be mediated through viral structural and nonstructural proteins N, ORF3b, ORF6, nsp1, and papain-like protease (6 -12).…”
mentioning
confidence: 99%